Right ventricular outflow tract electroanatomical abnormalities in asymptomatic and high‐risk symptomatic patients with Brugada syndrome: Evidence for a new risk stratification tool?. (7th October 2021) - Letsas, Konstantinos P.; Vlachos, Konstantinos; Conte, Giulio; Efremidis, Michael; Nakashima, Takashi; Duchateau, Josselin; Bazoukis, George; Frontera, Antonio; Mililis, Panagiotis; Tse, Gary; Cheniti, Ghassen; Takigawa, Masateru; et al.
Abstract: Introduction: Microstructural abnormalities at the epicardium of the right ventricular outflow tract (RVOT) may provide the arrhythmia substrate in Brugada syndrome (BrS). Endocardial unipolar electroanatomical mapping allows the identification of epicardial abnormalities. We evaluated the clinical implications of an abnormal endocardial substrate as perceived by high‐density electroanatomical mapping (HDEAM) in patients with BrS. Methods: Fourteen high‐risk BrS patients with aborted sudden cardiac death (SCD) (12 males, mean age: 41.9 ± 11.8 years) underwent combined endocardial‐epicardial HDEAM of the right ventricle/RVOT, while 40 asymptomatic patients (33 males, mean age: 42 ± 10.7 years) underwent endocardial HDEAM. Based on combined endocardial‐epicardial procedures, endocardial HDEAM was considered abnormal in the presence of low voltage areas (LVAs) more than 1 cm 2 with bipolar signals less than 1 mV and unipolar signals less than 5.3 mV. Programmed ventricular stimulation (PVS) was performed in all patients. Results: The endocardial unipolar LVAs were colocalized with epicardial bipolar LVAs ( p = .0027). Patients with aborted SCD exhibited significantly wider endocardial unipolar ( p < .01) and bipolar LVAs ( p < .01) compared with asymptomatic individuals. A substrate size of unipolar LVAs more than 14.5 cm 2 (area under the curve [AUC]: 0.92, p < .001] and bipolar LVAs more than 3.68 cm 2 (AUC: 0.82, p = .001) distinguished symptomatic from asymptomatic patients. Patients with ventricular fibrillation inducibility (23/54) demonstrated broader endocardial unipolar ( p < .001) and bipolar LVAs ( p < .001) than noninducible patients. The presence of unipolar LVAs more than 13.5 cm 2 (AUC: 0.95, p < .001) and bipolar LVAs more than 2.97 cm 2 (AUC: 0.78, p < .001) predicted a positive PVS. Conclusion: Extensive endocardial electroanatomical abnormalities identify high‐risk patients with BrS. Endocardial HDEAM may allow risk stratification of asymptomatic patients referred for PVS.